Share
Explore BrainMass

Find the particular solution of the differential equation : y=C(e^(-2x))sinx + C(e^(-2x))cos x y(0)= 1 y'(0)= 0

Find the particular solution of the general equation below, given the initial conditions.
Please show all details in the solution, simplifying if possible. Thank you.

y=C(e^(-2x))sinx + C(e^(-2x))cos x

y(0)= 1
y'(0)= 0

Solution Preview

We already have the general solution:

y=C1(e^(-2x))sinx+C2(e^(-2x))cosx
From the inition ...

Solution Summary

The particular solution of a differential equation is found.

$2.19